Hypericum and neem oil for dehisced post-surgical wounds: a randomised, controlled, single-blinded phase III study. (2nd June 2022) - Arena, Raimondo; Strazzeri, Maria Grazia; Bianchi, Tommaso; Peghetti, Angela; Merli, Yuri; Abbenante, Diego; Olivari, Diletta
Abstract : Objective: To evaluate the clinical efficacy of a hypericum and neem oil dressing, Primary Wound Dressing [ONE] (1PWD) (Kerecis AG, Switzerland), in a patient population with dehiscence of surgical wounds with critical colonisation/infection. Efficacy was defined as resolution of inflammatory/infective symptoms. Method: A randomised, controlled, single-blinded, parallel-arms phase III study was conducted comparing the experimental medication to silver-based dressings. All patients were evaluated at enrolment, on days 7, 14, 21 and 28. Improvement of inflammatory/infective symptoms was measured by detecting seven items of the Bates–Jensen Wound Assessment Tool (BWAT). Pain was assessed using the Numeric Rating Scale (NRS). Results: The study enrolled 99 patients. Follow-up was completed in 49 patients in the experimental group and 48 patients in the control group. Overall BWAT evaluation demonstrated similar outcomes between the groups: t=0.23, p-value=0.81, 95% confidence interval (CI): –13.3–10.8. Furthermore, when evaluating the seven items of the BWAT relating to inflammatory signs, there was not a significant difference between the groups: t=0.38, p=0.35, 95% CI: –2.8–2.7. However, when an analysis using the NRS pain scale was performed, a statistically significant pain reduction was demonstrated in favour of the experimental group: t=7.8, p<0.0001, 95% CI: 2.918–4.8819. Conclusion: This randomised controlled trial confirmed the efficacy of 1PWD, an investigational product, in the management of surgical dehiscence with critical colonisation or infection, with the added benefit of significant pain reduction when compared with a silver-based dressing.